Restorativeness mediates the effect of a brief virtual reality mindfulness exposure with a multi-ethnic group in a natural environment on global identity salience: a pilot study with adolescents - Russo, Claudia; Romano, Luciano; Clemente, Davide; Congiu, Alessia; Rodelli, Roberta; Navarini, Claudia; Panno, Angelo (Frontiers in Psychology, 2025)
IntroductionAdolescents are increasingly exposed to global challenges, making it important to promote a sense of global identity—defined as a psychological connection with humanity as a whole. While scholars have highlighted the role of mindfulness and restorativeness in promoting global identity per se, there is a lack of studies hypothesizing their involvement in a unique framework and adopting virtual reality (VR) as a tool. This study aimed to verify, in a sample of adolescents, the indirect effect of the exposure to a VR video of a group of multi-ethnic youths practicing a brief mindfulness session – compared to a VR video of a group of multi-ethnic youths involved in a volleyball play – on global identity through restorativeness.MethodsA quasi-experimental between-subjects design was adopted, involving 94 Italian adolescents randomly assigned to one of two conditions: (i) a 360-degree VR video showing a group of multi-ethnic youths practicing mindfulness in a natural environment or (ii) a 360-degree VR video showing a group of multi-ethnic youths playing volleyball in the same environment. We hypothesized that the VR exposure to the group of multi-ethnic youths practicing a brief mindfulness session – compared to the VR exposure to the group of multi-ethnic youths involved in a volleyball play - could enhance restorativeness, which in turn is expected to increase global identity salience.ResultsThe results of the mediation analysis supported our hypothesis, showing that participants exposed to the mindfulness condition – compared to the participants exposed to the volleyball play condition - reported significantly higher restorativeness, which in turn led to an increase in global identity salience [point estimate = 0.12, SE = 0.08, 95% CI = (0.004, 0.317)].DiscussionFindings shed light on the underlying processes involved in the exposure to a brief mindfulness session within a multi-ethnic group played in a virtual natural environment on global identity salience, emphasizing the mediating role of restorativeness. These results provide significant insights into the self-concept construction, which is critical in adolescence. Practical implications and future research directions are discussed.